On the distribution of Arioge germainii (Signoret) and Encedonia mutica (Signoret) (Heteroptera: Coreidae) - Faundez, Eduardo (My University, 2022)
The distribution of Arioge germainii and Encedonia mutica is reviewed and discussed. Some corrections are made on previous known localities for A. germainii and a new record from Maule Region in Chile is provided. The first specific locality data for E. mutica is provided, with records from Araucan??a region in Chile and Neuqu??n Province in Argentina.
Keywords: coreoidea; faunistics; hemiptera; new records